Basaloid squamous carcinoma of the anal canal with an adenoid cystic pattern: histologic and immunohistochemical reappraisal of an unusual variant. - Chetty, R; Serra, S; Hsieh, E (2005)
Two cases of a distinctive variety of basaloid squamous carcinoma (BSC) of the anal canal are described. Both occurred in female patients who presented with bleeding per rectum. Histologic evaluation of the tumors showed lobules and aggregates of medium-sized basaloid cells with distinctive peripheral palisading and focal areas of central, comedo-necrosis. Accompanying dysplasia of the overlying squamous mucosa was absent. However, the microscopic pattern was dominated by the presence of eosinophilic, hyaline, paucicellular basement membrane-like material around and within tumor nests. This appearance together with microcystic spaces simulated that of an adenoid cystic carcinoma. Immunohistochemistry of the tumors revealed the following profile: CK7, CK5/CK6, 34betaE12 positive, CK14 focally positive but CK20 negative. The following were all negative: EMA, CEA, smooth muscle and muscle-specific actin, calponin, and S-100. The tumor cells exhibited diffuse nuclear positivity with p63. The eosinophilic basement membrane hyaline material was positive for collagen type IV and also for laminin. BSC of the anal canal with an adenoid cystic pattern is an infrequently encountered and reported variant, although it is seen more often in the aerodigestive tract. There may be an increased propensity for BSC with an adenoid cystic pattern to metastasize to the liver, but the number of cases encountered are too small to be definitive. The histologic differential diagnosis is true salivary gland-type adenoid cystic carcinoma and basal cell adenocarcinoma. Immunohistochemistry and awareness of this unusual pattern of BSC will facilitate the correct diagnosis being reached.